2009
DOI: 10.1016/j.schres.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of NRG-1 and VAMP-1 in human brain aggregates exposed to clozapine

Abstract: Growing genetic evidence has implicated a role for neuregulin-1 (NRG-1) in schizophrenia pathogenesis as well as alterations in SNAP receptor (SNARE) proteins at both gene and protein levels in post-mortem investigations. In relation to a potential therapeutic mechanism for atypical antipsychotic medications, clozapine has been shown to increase both NRG-1 levels and synaptic markers in rodents. As evidence continues to mount for a potential restoration in connectivity by antipsychotic medications being a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Additionally, in a clinical study, after a 2-week treatment with risperidone and quetiapine, NRG1 mRNA expression of PBLs of first-onset schizophrenia patients (who has not take antipsychotics before) significantly increased compared to the levels before antipsychotic drug therapies (Zhang et al, 2008). Moreover, an in vitro study has shown that NRG1 protein expression increased in human fetal brain aggregates after being exposed to clozapine for three weeks; however, the expression of NRG1 proteins did not change following exposure to haloperidol (Chana et al, 2009). In addition to the finding that NRG1-induced ErbB4 activation was significantly enhanced in the PFC of schizophrenia patients (Hahn et al, 2006), it is very interesting that NRG1-induced ErbB4 activation was significantly reduced by a 12-weeks treatment with haloperidol in mouse brains (Hahn et al, 2006).…”
Section: The Effects Of Antipsychotic Treatment On Nrg1-erbb4 Signallingmentioning
confidence: 95%
“…Additionally, in a clinical study, after a 2-week treatment with risperidone and quetiapine, NRG1 mRNA expression of PBLs of first-onset schizophrenia patients (who has not take antipsychotics before) significantly increased compared to the levels before antipsychotic drug therapies (Zhang et al, 2008). Moreover, an in vitro study has shown that NRG1 protein expression increased in human fetal brain aggregates after being exposed to clozapine for three weeks; however, the expression of NRG1 proteins did not change following exposure to haloperidol (Chana et al, 2009). In addition to the finding that NRG1-induced ErbB4 activation was significantly enhanced in the PFC of schizophrenia patients (Hahn et al, 2006), it is very interesting that NRG1-induced ErbB4 activation was significantly reduced by a 12-weeks treatment with haloperidol in mouse brains (Hahn et al, 2006).…”
Section: The Effects Of Antipsychotic Treatment On Nrg1-erbb4 Signallingmentioning
confidence: 95%
“…Evidence from the present and previous studies reveals that various antipsychotics with various pharmacological binding profiles regulate NRG1-ErbB4 expression in distinct ways (Chana et al, 2009;Wang et al, 2008;Zhang et al, 2008). There is no evidence that antipsychotics could directly bind with ErbB4 receptors, although they do possess affinities for several G-protein coupled receptors (GPCRs), particularly dopamine D 2 receptors and serotonin 5-HT receptors (Correll, 2010;Kapur and Mamo, 2003).…”
Section: Discussionmentioning
confidence: 70%
“…upregulated NRG1 and ErbB4 expression in the hippocampus, but had no effect on expression in the PFC of rats (Wang et al, 2008). An in vitro study demonstrated that exposure to clozapine (but not haloperidol) for three weeks promoted NRG1 protein expression in human fetal brain aggregates (Chana et al, 2009). Differential effects of antipsychotic treatment in the expression of NRG1 have also been observed in blood samples.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations